Studi Literatur: Penyebab Terjadinya Anemia pada Remaja Putri: Studi Literatur: Penyebab Terjadinya Anemia Pada Remaja Putri - Feny Marselina; Ida Sofiyanti; Adelena; Atika Rizki Suryani; Rina Pratiwi; Tiya Kariyani (Universitas Ngudi Waluyo, 2022)
World Health Organization 2020 Global prevalence of anemia occurred in 204 countries from 1990 – 2019. Based on research data conducted in 2020, it was found that the total number of anemia cases increased from1.42 billion in 1990 to 1.74 billion in 2019. This study also shows The 3 regions theacontribute the highest anemia are West Africa, South Asia and Central Africa. Anemia is a condition when the body experiences a decrease or the number of red blood cells is below the normal range. This occurs due to a lack of hemoglobin (an iron-rich protein) that affects the production of red blood cells.Using a literature review study containing a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities. The description in this literature review is directed to develop a clear framework of thinking about solving the problems that have been described previously in the formulation of the problem. There is a relationship between nutritional status and knowledge with the incidence of anemia in adolescent girls. There are many causes of anemia in young women, based on the prevalence above, the authors are interested in taking a literature review study on the causes of anemia in young women.